New perspectives [on] computer concepts - Parsons, June Jamrich; Oja, Dan. (Boston, Mass. : Thomson/Course Technology, 2008)
Be engaged, excited and enlightened with New Perspectives on Computer Concepts, Tenth Edition. This book has been completely updated to provide you with the latest, most in-depth information on both computer concepts and the context in which they fit into today?s world. The Tenth More...Edition provides the most current information on computers, software, the Internet, and emerging issues and technologies. It's unique approach transforms learning concepts into a more approachable, hands-on experience that appeals to anyone, from the computer novice to the computer savvy learner
Orientation -- Chapter 1: Computers and Digital Basics -- Chapter 2: Computer Hardware -- Chapter 3: Computer Software -- Chapter 4: Operating Systems and File Management -- Chapter 5: LANs and WLANs -- Chapter 6: The Internet -- Chapter 7: The Web and E-mail -- Chapter 8: Digital Media -- Chapter 9: The Computer Industry: History, Careers, and Ethics -- Chapter 10: Information Systems Analysis and Design -- Chapter 11: Databases -- Chapter 12: Computer Programming
Accompanying BookOnCD contains the entire contents of the textbook with figures that come to life as videos, software tours, and animations. Includes also labs and computer-scored practice tests.
1
Keywords: Computers; Electronic digital computers; Electronic data processing